Trophic ecology of a Late Pleistocene early modern human from tropical Southeast Asia inferred from zinc isotopes. Issue 161 (December 2021) - Bourgon, Nicolas; Jaouen, Klervia; Bacon, Anne-Marie; Dufour, Elise; McCormack, Jeremy; Tran, N.-Han; Trost, Manuel; Fiorillo, Denis; Dunn, Tyler E.; Zanolli, Clément; Zachwieja, Alexandra; Duringer, Philippe; et al.
Abstract: Tam Pà Ling, a cave site in northeastern Laos, has yielded the earliest skeletal evidence of Homo sapiens in mainland Southeast Asia. The reliance of Pleistocene humans in rainforest settings on plant or animal resources is still largely unstudied, mainly due to poor collagen preservation in fossils from tropical environments precluding stable nitrogen isotope analysis, the classical trophic level proxy. However, isotopic ratios of zinc (Zn) in bioapatite constitute a promising proxy to infer trophic and dietary information from fossil vertebrates, even under adverse tropical taphonomic conditions. Here, we analyzed the zinc isotope composition ( 66 Zn/ 64 Zn expressed as δ 66 Zn value) in the enamel of two teeth of the Late Pleistocene (63–46 ka) H. sapiens individual (TPL1) from Tam Pà Ling, as well as 76 mammal teeth from the same site and the nearby Nam Lot cave. The human individual exhibits relatively low enamel δ 66 Zn values (+0.24‰) consistent with an omnivorous diet, suggesting a dietary reliance on both plant and animal matter. These findings offer direct evidence of the broad utilization of resources from tropical rainforests by one of the earliest known anatomically modern humans in Southeast Asia.